A Longitudinal Study of Severe Acute Respiratory Syndrome Coronavirus 2 Antibody Response in a Subset of United States Blood Donors. (28th December 2022) - Tonnetti, Laura; Dodd, Roger Y; Burke, Donna D; Saá, Paula; Spencer, Bryan R; Xu, Meng; Haynes, James M; Stramer, Susan L
Abstract: Background: Blood donors were tested for antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); resulting antibody levels were monitored over time. Methods: Donors reactive to anti-SARS-CoV-2 spike protein (S1-total antibodies) participated in a follow-up study of 18 months. Testing for nucleocapsid antibodies distinguished between vaccination and infection. Vaccination and symptom information were collected for anti-S1-reactive donors by completing a survey. Results: The majority of 249 followed donors were over 60 years old (54%), White (90%), and female (58%); 83% had not been vaccinated at enrollment, but by study completion, only 29% remained nonvaccinated. Of the 210 (84%) anti-N-reactive donors, 138 (66%) reported vaccination, whereas 37 (95%) of donors vaccinated and anti-N negative at enrollment remained uninfected. Vaccinated (2 doses) and infected donors showed a steady increase in anti-S1 that increased markedly for vaccinated donors after a booster and infected donors after vaccination (slightly higher for those with hybrid immunity), whereas anti-N levels declined. Most surveyed nonvaccinated donors (65%) reported symptoms, whereas 85% of vaccinated donors were asymptomatic. A coronavirus disease 2019 (COVID-19) diagnosis was reported by 48 (31%) nonvaccinated and 3 (8%) vaccinated donors. Of asymptomatic donors, 38% never tested diagnostically for COVID-19, and 35% tested negative, suggesting an absence of knowledge of the infection. Conclusions: Healthy blood donors were vaccinated at high rates and remained mostly asymptomatic and noninfected, whereas approximately two thirds of infected donors reported symptoms. Anti-S1 levels increased while anti-N decreased over 18 months but remained comparable between vaccinated and hybrid immune individuals with dramatic anti-S1 increases after vaccination or boosting. Abstract : Blood donors were COVID-19-vaccinated and/or infected at high rates. Nonvaccinated donors reported a positive COVID-19 diagnosis and symptoms more frequently than vaccinated donors. Spike-antibody levels were maintained at 18 months increasing after vaccination or boosting while nucleocapsid antibodies slowly decreased.